Parents' conceptions of their children's oncological condition and their chemotherapeutic treatment - Fernanda Machado Silva-Rodrigues; Verônica Leticia da Silva Vulczak; Carolina Fonseca Alencar; Luciana Soares Costa Santos; Lucila Castanheira Nascimento (Universidade Federal de Santa Maria, 2020)
Objective: to assess and analyze the conceptions of fathers and mothers of children with cancer of their children's disease and their chemotherapeutic treatment according to the concepts of the Commonsense Model (CSM). Method: descriptive, qualitative study. Fourteen (14) parents of pediatric patients undergoing cancer treatment were interviewed. The data underwent content analysis and were analyzed according to the CSM. Results: the results were grouped into the following categories: Disease identity: conceptions of cancer; Duration: the length of time up to diagnosis and symptoms involved; Causes of the disease: the search for explanations; Consequences of the disease and treatment; Cure or control: perceptions of the prognosis as based on the CSM domains. Conclusion: negative conceptions relating to cancer and its treatment can cause uncertainties affecting the parents, compromise the use of resources to cope with the consequences of the disease, and reduce the expectations that the experience will have a positive outcome.